Pengaruh Leverage dan Return On Assets terhadap Tax Avoidance dengan Proporsi Komisaris Independen sebagai Variabel Moderasi - Yulyani, Evita; Suhono; Akbar, Nahruddien; Avionita, Venni (The Double Entry Journal, 2022)
This study aims to obtain empirical evidence and determine the effect of Leverage and Return On Assets on Tax Avoidance with the Proportion of Independent Commissioners as the moderating variable. This research is a quantitative study with 16 (sixteen) research samples taken from the entire population of coal mining companies listed on the Indonesia Stock Exchange in 2016-2019. The data used in this study is secondary data in the form of annual reports obtained from the Indonesia Stock Exchange website and each company that is the sample. The data analysis technique used IBM SPSS Statistics 21. The results showed that leverage had no effect on tax avoidance. Return on assets has a negative and significant effect on tax avoidance. Leverage and return on assets have no effect on tax avoidance simultaneously. The proportion of independent commissioners does not moderate the effect of leverage on tax avoidance. The proportion of independent commissioners does not moderate the effect of return on assets on tax avoidance.